Author Correction: Rare variants in drug target genes contributing to complex diseases, phenome-wide. Issue 1 (December 2018) - Verma, Shefali; Josyula, Navya; Verma, Anurag; Zhang, Xinyuan; Veturi, Yogasudha; Dewey, Frederick; Hartzel, Dustin; Lavage, Daniel; Leader, Joe; Ritchie, Marylyn; Pendergrass, Sarah
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.